The effects of clown intervention on worries and emotional responses in children undergoing surgery - Fernandes, Sara (2010)
This study investigated whether clown intervention could reduce preoperative worries and the affective responses of children undergoing minor surgery. Parental anxiety was also tested. Child’s age, previous hospitalization, and temperament were tested as predictors of the child’s responses during this preoperative phase. Seventy children were assigned to one of two groups: children accompanied by their parents and a pair of clowns or, those accompanied by the parents but without the clowns. The results emphasized the relevance of clown intervention on the reduction of preoperative worries and emotional responses, not only in children but also in their parents.